2019
DOI: 10.1080/20009666.2019.1571880
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated myositis: an elusive entity

Abstract: Inflammatory myopathies are characterized by the skeletal muscle inflammation leading to symptoms of myopathy along with varying involvement of other organs such as lung, skin and joints. The strong association between inflammatory myopathies and malignancy has been well recognized. Recently, ‘cancer-associated myositis (CAM)’, has been proposed to be a paraneoplastic syndrome due to the anti-tumor immunity secondary to similar tumor and regenerating muscle antigens.As the prognosis of myositis depends on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The exact mechanism of this relationship between cancer and dermatomyositis has yet to be elucidated. The term cancer‐associated myositis has been proposed as a paraneoplastic syndrome 21 . High‐risk features associated with cancer‐associated myositis include old age, dermatomyositis, absence of interstitial lung disease, severe cutaneous necrotizing inflammation on biopsy, poor response to myositis treatment, 21 and dysphagia 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact mechanism of this relationship between cancer and dermatomyositis has yet to be elucidated. The term cancer‐associated myositis has been proposed as a paraneoplastic syndrome 21 . High‐risk features associated with cancer‐associated myositis include old age, dermatomyositis, absence of interstitial lung disease, severe cutaneous necrotizing inflammation on biopsy, poor response to myositis treatment, 21 and dysphagia 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The term cancer‐associated myositis has been proposed as a paraneoplastic syndrome 21 . High‐risk features associated with cancer‐associated myositis include old age, dermatomyositis, absence of interstitial lung disease, severe cutaneous necrotizing inflammation on biopsy, poor response to myositis treatment, 21 and dysphagia 22 . The most suggestive risk of cancer in myositis is associated with autoantibodies anti‐TIF1‐gamma and antinuclear matrix protein‐2 22 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent review defines cancer-associated myopathy (CAM) as myopathy that occurs two years before or three years after the diagnosis of cancer [ 48 ]. There are four possible forms of myositis described: dermatomyositis (DM), polymyositis (PM), necrotizing myopathy (NM), and inclusion body myositis (IBM).…”
Section: Discussionmentioning
confidence: 99%
“…CAM is resistant to standard treatment but usually improves after treating the underlying neoplasia; additionally, recurrence of cancer has been associated with relapse of CAM [ 61 ]. Due to the high incidence of cancer during the first three years of myositis, annual cancer surveillance must be emphasized for the first three to four years [ 48 , 62 ]. Recommended surveillance is a complete pelvic/prostate examination, chest radiography, and age and gender-appropriate cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…1 Multiple epidemiological studies have reported an association between inflammatory myopathies and cancer, strongly linked with DM. [2][3][4] It has been demonstrated that even 1/3 of patients with DM may present malignancy in the 3 years after DM diagnosis. An exact explanation for this relationship remains unknown, although it may be related to altered cellular and humoral immunity.…”
Section: Introductionmentioning
confidence: 99%